Insecticidal Components from the Essential Oil of Chinese Medicinal Herb, Ligusticum chuanxiong Hort - Sha Sha Chu; Guo Hua Jiang; Zhi Long Liu (E-Journal of Chemistry)
Essential oil of Chinese medicinal herb, Ligusticum chuanxiong dried rhizome was found to possess insecticidal activity against maize weevils, Sitophilus zeamais. The main components of L. chuanxiong essential oil were Z-3-butylidenephthalide (20.56%), Z-ligustilide (19.61%), 4-terpinenol (8.82%), 4-vinylguaiacol (6.81%) and α-selinene (6.01%). Bioactivity-guided chromatographic separation of the essential oil on repeated silica gel columns led to isolate three compounds namely 3-butylidenephthalide, Z-ligustilide and 4-vinylguaiacol. Z-liqustilide and Z-3-butylidenephthalide showed pronounced toxicity against S. zeamais (LD50= 10.23 and 15.81 μg/adult respectively) and were more toxic than 4-vinylguaiacol (LD50 = 63.75 μg/adult). The crude essential oil also possessed contact toxicity against S. zeamais (LD50 = 13.09 μg/adult).